Protection from Vampire Attacks on Routing Protocol (International Journal of Engineering and Computer Science, 2017)
In  sensing  and  pervasive  computing  ad-hoc low-power  wireless  networks  are  an  exciting  research. Prior security work has first focused on denial of communication  at the routing  or levels  of  media access control. This paper examine resource depletion attacks  at routing protocol layer, which disable networks by quickly draining node's battery power. These “Vampire” attacks are not specific to any particular protocol, but rather depend on the properties  of many well known classes of routing protocols. We find that all examined protocols are affected to Vampire attacks ,which are destructing, hard to detect, and are easy to carry out using as few as one malicious  insider  sending  only  protocol  compliant messages. In case of worst case, a single Vampire can increase network-wide energy usage by a factor of O(N), where N in the number of nodes of network. The methods we discuss to mitigate these types of attacks which includes a new proof-of- concept protocol that bounds the damage caused by Vampires during the packet forwarding phase.